PENGARUH BIAYA OPERASIONAL PENDAPATAN OPERASIONAL DAN LIKUIDITAS TERHADAP RETURN ON ASSET (STUDI KASUS PT BANK TABUNGAN NEGARA INDONESIA TAHUN 2018-2022 - Muhammad Distian Andi Hermawan (Jurnal Kajian Ekonomi dan Manajemen Indonesia (JKEMI), 2023)
This study aims to see the effect between operational costs operating income and liquidity on return on assets. Either partially or simultaneously. The method of analysis used in this study is a statistical method in which the data source used is secondary data sourced from the Indonesia Stock Exchange, which this method is to determine the effect of operating expenses on operational income and liquidity on return on assets. This study uses multiple linear regression analysis by first testing classical assumptions, namely normality, multicollinearity, and heteroestensity and autocorrelation tests. The results of the data processing above show that variable X1, namely the operational cost of bopo operating income on return on assets with a significance level of 0.22, which is greater than 0.05, it can be said that variable X1 on y has no partial effect and for variable X2 liquidity with a significance value of 0.361 greater than 0.05, it can be concluded that variable X2 has no effect on variable y partially.